Acute headache and persistent headache attributed to cervical artery dissection: Field testing of ICHD-III beta. (August 2014) - Schytz, Henrik W; Ashina, Messoud; Magyari, Melinda; Larsen, Vibeke A; Olesen, Jes; Iversen, Helle K
The criteria for headache attributed to cervical artery dissection have been changed in the new third edition of the International Classification of Headache Disorders (ICHD-III beta). We have retrospectively investigated 19 patients diagnosed from 2001 to 2006 with cervical artery dissection at onset and followed them up six months after dissection. At dissection onset 17/19 patients were classified as headache probably attributed to vascular disorder at the time of dissection using the ICHD second edition (ICHD-II) criteria. In contrast, 17/19 of patients fulfilled the ICHD-III beta criteria for Headache or facial or neck pain attributed to cervical carotid or vertebral artery dissection or Headache attributed to intracranial arterial dissection . Six months after dissection five of 19 patients still reported persistent headache attributed to dissection. The study demonstrates that the ICHD-III beta criteria for cervical artery dissection are useful for classifying patients at the first encounter. We show for the first time that persistent headache attributed to arterial dissection is frequent.